Towards an integrated Jurassic biostratigraphy for eastern Greenland - Kelly, Simon R.A.; Gregory, F. J.; Braham, W.; Strogen, D. P.; Whittham, A. (Volumina Jurassica, 2015)
The thick and relatively complete Jurassic succession of eastern Greenland provides a unique biostratigraphic record for the North Atlantic region. The main biostratigraphic control for the succession has been provided by molluscs, especially ammonites and to a lesser extent by bivalves and belemnites. The late John Callomon and colleagues recognised 93 Boreal ammonite-bearing horizons in the Mid to Late Jurassic. This provides a reliable backbone to the biostratigraphy of these strata, prompting a palynological colleague to comment that they are the “Policemen of Jurassic Stratigraphy”. Other biostratigraphically significant microfossil and palynological groups, can be calibrated against this standard, but on their own cannot achieve the same precision. The Early Jurassic of eastern Greenland does not have such fine control as later parts of the period. No single biostratigraphic group can be used successfully throughout the interval, and there are only three significant ammonite faunas during this period. Reliance on various different organisms is necessary to cope with the changing range of marine to non-marine environments. CASP field-work from 1990 to 2012 has resulted in the collection of much biostratigraphic material. In this article, published data are summarised together with previously unpublished data in the form of a unified table. The integrated chart shows detailed columns for the whole eastern Greenland Jurassic. It demonstrates the ammonite, palynological and microfossil events/biozones and horizons which are correlated by time. More limited information is available on belemnites, bivalves and macroflora. This is the first time such an integrated biostratigraphic scheme has been assembled for the Jurassic of eastern Greenland. It will be of value to the offshore oil-industry in the northern North Atlantic and on the Barents Shelf as well as to field geologists in Greenland.